"Keep Talking to Me": College-Attending Women's Desires for Support from Mothers, Fathers, and Friends/Peers in Healthy Sexual Decision-Making. - Astle, Shelby M.; Anders, Kristin M.; Shigeto, Aya; Rajesh, Priya (Archives of Sexual Behavior, 2023)
Emerging adulthood (ages 18–29) is a transitional life stage characterized by changes in identity and sexual development, including navigating new sexual experiences and cultures. During this transitional period, emerging adult women often continue to seek the support of their parent(s), while also increasing their reliance on friends/peers. However, little is known about what specifically college-attending emerging adult women desire from these support systems when it comes to making healthy sexual decisions. Using thematic analysis, we examined what emerging adult women (N = 192) identified as support they desire to receive from mothers, fathers, and friends/peers in making healthy sexual decisions while in college. Overall, the majority of participants reported desires to receive some form of sexual support from the majority of sources. There were four themes of desired support across sources: (1) Advice and Communication, (2) Nothing, (3) Emotional and Tangible Support, and (4) Attitude Shifts. Differences in types of desired support were also found across different sources with participants reporting desires for emotional support from their mothers, no desired support from their fathers, and direct interventions from their friends. Implications for informing sexuality educators and programs are discussed.